A registry-based study of tooth-colored restorative materials for decayed teeth in Taiwan - Ni-Yu Su; Yu-Hsun Wang; Yu-Chao Chang (Elsevier, 2023)
Background/purpose: As esthetic demands with direct restorations, tooth-colored materials were used to replace amalgam filling gradually. However, little is known about the tooth-colored restorative materials for decayed teeth in Taiwan. In this study, the use of composite resin, glass ionomer cement, and compomer was analyzed by National Health Insurance Research Database (NHIRD). Materials and methods: A retrospective study was conducted to analyze the registered database compiled by Taiwanese NHIRD from 1997 to 2013. The results were further to analyze the application of tooth-colored restorative materials by sex and age. In addition, time trends of dental visits for each tooth-colored restorative material were also investigated. Results: The average annual composite resin filling (CRF) ratio was 18.41% of nationwide population in Taiwan. The prevalence of CRF stratified by sex and age was significantly increased from 1997 to 2013 (P for trend <0.0001). The time trends of dental visits for CRF were significantly increased (P for trend <0.0001). The average annual glass ionomer cement filling (GICF) ratio was 1.79% of Taiwanese population. The prevalence of GICF stratified by sex and age was demonstrated a decreased pattern (P for trend <0.0001). The time trends of dental visits for GICF were significantly decreased (P for trend <0.0001). The average annual compomer filling ratio was 0.57% of whole population in Taiwan. Conclusion: Form the results of this registry-based study, a significant increased trend of CRF for decayed teeth was observed in Taiwanese population during past 17 years.